Aspek Religi Dalam Kumpulan Puisi Antologi Puisi Mahabbah Karya Iqoh Umar: Kajian Semiotik Dan Implementasinya Dalam Pembelajaran Sastra Di SMA - Nurhayati, Tira; , Prof. Dr. Ali Imron Al-Ma'ruf, M.Hum (2016)
The purpose of this study is to describe, (1) structures that build up a poetryMahabbah Poetry Antalogy by Iqoh Umar, (2) religious aspects that contained in poetryMahabbah Poetry Antalogy by Iqoh Umar, and (3) the implementation of the research in the poetryMahabbah Poetry Antalogy by Iqoh Umar. This research used qualitative descriptive methods. The data in this research is the line in each stanza's poem that shaped of religious aspects contained in a set of poetryMahabbah Poetry Antalogy by Iqoh Umar. The sources of data in this research area set of poetryMahabbah Poetry Antalogy by Iqoh Umar, March 2014 and 150 pages thick. Methodof collecting data used interview techniques, libraries, record, and listen. Method of data analyzed used reading semiotic model that consists of heuristic and hermeneutic reading. There are three results of this study, i.e. (1) Forming elements of poetry such as theme, feelings, diction, imagination, concrete words, figurative language, diversification, and the moral value. (2) The religious aspect in poetry Mahabbah Poetry Antalogy by Iqoh Umar consists of religious emotion, belief systems, religious ceremonies system, and the people who embrace religion. The most dominant religion aspect is religious emotion, and (3) this research can be implemented in the learning of literature in high school grade X in first semester with the competence standards listening 5.Understanding the poetry that delivered directly / indirectly and the basic competencies 5.1identify the elements form a poem that delivered directly or indirectly and the basic competencies 5.2 reveals the content of a poem delivered directly or through recording. Based on analyze set of poetryMahabbah Poetry Antalogy by Iqoh Umar religious aspect encourages students to act and be have with the values and norms that exist in society.Religious aspects can also build student's faith in God in accordance with the teachings that have been embraced. Keywords: The religious aspects, Mahabbah Poetry Antalogy, semiotics, literary learning in senior high school.